Limiting stochastic processes of shift-periodic dynamical systems. Issue 11 (27th November 2019) - Stadlmann, Julia; Erban, Radek
Abstract : A shift-periodic map is a one-dimensional map from the real line to itself which is periodic up to a linear translation and allowed to have singularities. It is shown that iterative sequences x n +1 = F ( x n ) generated by such maps display rich dynamical behaviour. The integer parts ⌊ x n ⌋ give a discrete-time random walk for a suitable initial distribution of x 0 and converge in certain limits to Brownian motion or more general Lévy processes. Furthermore, for certain shift-periodic maps with small holes on [0, 1], convergence of trajectories to a continuous-time random walk is shown in a limit.